P-31 ACUTE LIVER FAILURE DUE TO WILSON'S DISEASE IN COSTA RICA: A LOOK AT GENETICS - Jorge Andres Herrera Corrales; Francisco Hevia Urrutia; Danny Alvarado; Fernanda Vasquez Carit; Francisco Vargas Navarro; Jorge Eduardo Vargas Madrigal; Karina Hidalgo; Mildred Jimenez (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Acute liver failure (ALF) can be defined as a complex clinical syndrome characterized by coagulopathy, alteration in liver biochemistry and encephalopathy in a patient without underlying chronic liver disease. An exception occurs in patients with Wilson's Disease (WD) manifested precisely by ALF. Costa Rica is known as a country with a high incidence of WD, a pioneer in the study of the genetics of this disease, documenting more than 1,161 pathogenic variants. Taking advantage of the work of the genetics laboratory of the National Children's Hospital, we undertook the task of assessing the genetic spectrum of patients with FHA due to Wilson in the last 2 years in our country. Objective: To analyze and describe the genetic spectrum of acute liver failure due to WD in Costa Rica during the last two years. Patients / Materials and Methods: Molecular Sequencing (Sanger NGS) for molecular confirmation, as well as MLPA techniques and Copy Number Variation Analysis (CNVs). Results and Discussion: During the period (2022-2023), 86 patients with WD variants were identified, of which 30 had confirmatory genetics of the disease. 4 of them presented as having FHA, being managed with a liver transplant, and to this day all of them are alive. It was evident that 100% of the patients presented the c.3809A>G variant, with half of the patients being homozygous and the other half being c.3207C>A / c.3809A>G compound heterozygotes. Conclusions: The c.3809A>G variant was found in all patients who presented ALF due to Wilson's disease in Costa Rica in the last 2 years. There is a lack of studies that assess the association between this variant and more aggressive presentations of the disease, however these results allow us to open a debate about the study of genetics as a predictor of ALF due to WD.